Pengaruh Religiusitas, Kecerdasan Emosional, Kecerdasan Intelektual, Idealisme dan Status Ekonomi Terhadap Persepsi Etis Mahasiswa Akuntansi - Rozikin, Khoirur; Susilowati, Endah (Rifa'Institute, 2023)
The purpose of this research was to test and prove the effect of reli giosity, emotional intelligence, intellectual intelligence, idealism and economic status on ethical perceptions of accounting students. The data used in this study is quantitative data. This research uses a data collection method, namely the questionnaire method. The questionnaire in this study will be given to respondents, namely UPN